1989
DOI: 10.1021/la00085a025
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization of calcium hydroxylapatite by Fourier transform infrared spectroscopy

Abstract: the bulk equilibrium value cannot be explained by the heat effects.(c) The surface charge may alter the interfacial equilibrium. In the present study the charge on the droplets ranged from lo4 to lOe elementary charges. For the droplet size range (2 pm 5 a 5 20 pm) encountered in this study the effect of surface charge density on the equilibrium composition is negligible. Moreover, the observed moisture content shows no correlation with the surface charge density. ConclusionsWe have measured the evaporation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(137 citation statements)
references
References 3 publications
9
123
0
2
Order By: Relevance
“…HA was synthesized by the slow addition of 0.6 M H 3 PO 4 to an aqueous suspension of 1.0 M Ca(OH) 2 under constant heating at 150°C in N 2 atmosphere as per the method reported in literature [14]. In order to obtain uniform size crystals of HA the pH of the reaction mixture was strictly controlled i.e.…”
Section: Synthesis Of Hamentioning
confidence: 99%
“…HA was synthesized by the slow addition of 0.6 M H 3 PO 4 to an aqueous suspension of 1.0 M Ca(OH) 2 under constant heating at 150°C in N 2 atmosphere as per the method reported in literature [14]. In order to obtain uniform size crystals of HA the pH of the reaction mixture was strictly controlled i.e.…”
Section: Synthesis Of Hamentioning
confidence: 99%
“…3-ions to compensate the cation deficiency of CaHap 40,42 . By replacement of Ca 2+ ions by Mn ones, the sharpness of 3572 cm -1 band is steeply weakened at XMn≤0.04.…”
Section: In Vacuo Ir Measurementsmentioning
confidence: 99%
“…At the same time, 3628 and 3655 cm -1 bands are weakened at XMn≥0.08 but 3681 cm -1 band remains. It was reported that the acidic surface P-OH groups exhibit blue shift and appears at higher wavenumber such as 3681 cm -1 42 . Therefore, the blue shift observed for surface P-OH bands in Fig.…”
Section: In Vacuo Ir Measurementsmentioning
confidence: 99%
“…20) Ishikawa et al reported that surface POH groups for the pure Ca deficient highly crystallized Hap particle will be appeared at 3659, 3673 and 3682 cm ¹1 . 20) The single POH peak at 3680 cm ¹1 for AE particles could be due to the low crystallinity with aggregated crystal structure of these particles. Similar result was observed on the Hap particles produced from the Ca(OH) 2 -tpp system as reported previously.…”
Section: ¹1mentioning
confidence: 99%